Analisis Pelaksanaan Stimulasi Deteksi Intervensi Dini Tumbuh Kembang (SDIDTK) di Upt Puskesmas Sungai Piring - Rosa Handayani; Nurlisis; Nur' Afni (Jurnal Kesehatan Komunitas, 2020)
The Early Detection and Intervention Program for Growth and Development (SDIDTK) is a comprehensive quality growth and development program for children through the early detection and intervention growth and development program during the first five years of life. The SDIDTK program at Sungai Piring Health Center is still faced with less than optimal management at various stages. Objective of the study is to determine the implementation of SDIDTK at Sungai Piring Health Center in 2019. Qualitative study was conducted. Data collection used in-deep interviews, the field observation in at Health Center, Integrated Healthcare Center, home visits, and tracking of related documents that supporting unit to complete residency report. The informant was the head of the Health Center, the head of administration, the person responsible for the SDIDTK program, the responsible person for the Integrated Healthcare Center, cadre and mothers who brought their children under five Health Center and Integrated Healthcare Center. Result showed the number of health workers were lack, in addition to SDIDTK officer was also responsible for other programs and never received SDIDTK training. The lack of planning, implementation had not been effective and monitoring and evaluation of SDIDTK implementation had not been sustainable. The availability of facilities and infrastructure was not sufficient enough. Funds had been budgeted but utilization had not been maximized. Recording and reporting were not going well. The conclusion is early Growth and Stimulation, Detection, and Intervention Activities (SDIDTK) have not been carried out optimally. Puskesmas are expected to be able to improve the planning, effectiveness of implementation, evaluation monitoring, and follow-up to the SDIDTK program.    Keywords:  Implementation, stimulation, growth development